The postgraduate research handbook : succeed with your MA, MPhil, EdD and PhD / Gina Wisker. - Wisker, Gina, 1951- (Palgrave Study Guides, 2001)
A guide through research for all postgraduate students including international students, largely involved in MA, MPhil, EdD and PhD study. Advice, support and both active and reflective tasks take readers through the stages of research.